CBDC ADOPTION: ALIGNING MODEL TECHNOSTRESS INHIBITORS AND PERCEIVED VALUE AMONG INDONESIAN GENERATION Z - Febriyanto, Ahmad; Adenia, Niniek; Annabila, Isfiya; Yusfiarto, Rizaldi (Bank Indonesia, 2025)
In recent years, central banks have been left scrambling to respond to the increase in Cryptocurrency transactions by establishing legitimate digital currencies called Central Bank Digital Currency (CBDC). The success of CBDC programmes will be closely tied to the public interest in adopting CBDC. Given the emerging influence of those born into what is commonly known as Generation Z, this research involved 329 Indonesians identifying as Generation Z to determine factors affecting the adoption of Indonesian CBDC. All data were analysed using Structural Equation Modelling Partial Least Square (SEM-PLS). The results show that the main determinants driving Generation Z’s interest in adopting CBDC are perceived value (epistemic, monetary, and convenience value) and general trust. Technostress inhibitors (facilitation of literacy and engagement facilitation) tended to influence Generation Z’s trust. General trust in this study also shows a partial moderating effect in the relationship between perceived value and intention to use CBDC and a full moderation effect on the relationship between technostress inhibitors and intention to use CBDC. The findings of this study provide advice to Bank Indonesia on how to increase the usefulness of CBDC related to monetary value and the value derived from the ease of use of CBDC to maintain public trust and increase public interest.